Penerapan Metode Bercerita dan Bernyanyi Untuk Meningkatkan Hasil Belajar Agama Hindu Siswa Kelas III Semester I SD Negeri 1 Dukuh - I Nyoman Menget Adriasa (Jayapangus Press, 2021)
The purpose of this study was to improve student learning outcomes in the subjects of Hindu Religion Class III SD Negeri 1 Dukuh through the application of singing and storytelling methods in learning Hindu Religious Education. This classroom action research was carried out in two cycles. The subjects of this study were the third grade students of SD Negeri 1 Dukuh, totaling 16 people consisting of 8 female students and 8 male students. Data were collected by observation and learning outcomes tests. The collected data was then analyzed by qualitative descriptive statistics. The results showed that the application of storytelling and singing methods could improve student learning outcomes. This can be seen from the average learning outcomes, absorption and classical mastery of students in cycle I to cycle II which increased. The average value of the first cycle reached 76.25 and the second cycle reached 82.50. That means, the average value from cycle I to cycle II has increased by 6.25. Likewise for student absorption. Classical completeness of students in the first cycle was 68.75% with 11 students completed and 5 students incomplete. Furthermore, in the second cycle of classical completeness 100% with 16 students completed. Based on these data, students' classical mastery between cycle I and cycle II increased by 31.25%. Based on these results, several suggestions can be recommended, namely: Hindu Religious Education teachers are expected to apply storytelling and singing methods to improve student learning outcomes. students.